UTILIZATION OF COASTAL ZONE IN INDONESIA. PRESENT STATUS OF OYSTER, SEAWEED AND COCKLE CULTURE - Ismail, Wardana (Marine Research in Indonesia, 1977)
Maricullure in coastal zone, such as the bays, inlets, or lagoons in coral reef is becoming more important in the world fishery activities. In Indonesia, some culture experiments are being conducted, such as for oyster (Crassostrea tuculata BORN) in Banten Bay, and seaweed (Eucheuma spinosum) in Samaringa Islands (Central Sulawesi) and Talang islands (Riau Archipelago), while culture of cockle (Anadara granose LIN.) based on a simple method have been conducted by local fishermen from Ketapang (West Jawa) since several years ago. Some preliminary results of culture experiments are given.